The impact of adipose tissue distribution on endometrial cancer: a systematic review - Bosch, Anouk A. S. van den; Pijnenborg, Johanna M. A.; Romano, Andrea; Winkens, Bjorn; Putten, Louis J. M. van der; Kruitwagen, Roy F. P. M.; Werner, Henrica M. J. (Frontiers in Oncology, 2023)
Introduction Endometrial cancer (EC) is the most common gynecological cancer with a rising incidence, attributed to advanced life expectancy and obesity. Adipose tissue (AT) is an important endocrine organ and its metabolic activity is affected by the different anatomical distribution or locations. AT distribution influences a number of diseases. In EC, it remains unclear whether the type of AT distribution impacts development or prognosis. This systematic review aimed to determine whether AT distribution is associated with patient characteristics, disease characteristics and patient prognosis in EC. Materials and methods A search was conducted in Medline, MEDLINE EMBASE and Cochrane library. Studies were included that enrolled EC patients with any histological subtype and that distinguished between the visceral and subcutaneous AT compartment In eligible studies, correlative analyses were performed for all outcome measures and AT distribution. Results Eleven retrospective studies were included, with a wide range of measurements for the visceral and subcutaneous AT compartments. AT distribution was found to be significantly correlated to a number of relevant (disease) characteristics including obesity measures, histological subtype, lymph node metastasis and sex steroid levels. Further, increased visceral AT volume was statistically significant associated with a worse survival (OS, DSS and PFS). Discussion/Conclusion This review demonstrates there are significant correlations between AT distribution and prognosis, BMI, sex steroid levels and disease characteristics like histology. Well-designed, prospective and larger-scale studies are needed to pinpoint these differences more specifically and understand how it can add in prediction, and even therapy in EC.